EFSUMB Clinical Practice Guidelines for Point-of-Care Ultrasound: Part One (Common Heart and Pulmonary Applications) SHORT VERSION - Jarman, Robert David; Colclough, Anna; McDermott, Cian; Bøtker, Morten; Knudsen, Lars; Harris, Tim; Albaroudi, Bilal; Albaroudi, Omar; Haddad, Mahmoud; Darke, Robert; Berry, Edward; Breslin, Tomas; Fitzpatrick, Gareth; Flanagan, Leah; Olusanya, Olusegun; Craver, Dominic; Omar, Adhnan; Simpson, Thomas; Cherian, Nishant; Dore, Martin; Prosen, Gregor; Kay, Sharon; Villén-Villegas, Tomás; Gargani, Luna; Carley, Simon; Woo, Michael; Dupriez, Florence; Hussain, Arif; Via, Gabriele; Connolly, James Anthony; Peck, Marcus; Melniker, Larry; Walden, Andrew; Attard Biancardi, Mark Anthony; Żmijewska-Kaczor, Olga; Lalande, Elizabeth; Geukens, Paul; McLaughlin, Russell; Olszynski, Paul; Hoffmann, Beatrice; Chin, Eric; Muhr, Christopher; Kim, Daniel J.; Mercieca, Andre; Shukla, Dharmesh; Hayward, Simon; Smith, Michael; Gaspari, Romolo; Smallwood, Nick; Pes, Philippe; Tavazzi, Guido; Corradi, Francesco; Lambert, Michael; Morris, Craig; Trauer, Michael; Baker, Kylie; Bystrzycki, Adam; Goudie, Adrian; Liu, Rachel; Rudd, Lynne; Dietrich, Christoph F.; Jenssen, Christian; Sidhu, Paul S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Objective To evaluate the evidence and produce a summary and recommendations for the most common heart and lung point-of-care ultrasound (PoCUS).Methods We reviewed 10 clinical domains/questions related to common heart and lung applications of PoCUS. Following review of the evidence, a summary and recommendations were produced, including assigning levels of evidence (LoE) and grading of recommendation, assessment, development, and evaluation (GRADE). 38 international experts, the expert review group (ERG), were invited to review the evidence presented for each question. A level of agreement of over 75 % was required to progress to the next section. The ERG then reviewed and indicated their level of agreement of the summary and recommendation for each question (using a 5-point Likert scale), which was approved in the case of a level of agreement of greater than 75 %. A level of agreement was defined as a summary of “strongly agree” and “agree” on the Likert scale responses.Findings and Recommendations One question achieved a strong consensus for an assigned LoE of 3 and a weak GRADE recommendation (question 1), the remaining 9 questions achieved broad agreement with an assigned LoE of 4 and a weak GRADE recommendation (question 2), three achieved an LoE of 3 with a weak GRADE recommendation (questions 3–5), three achieved an LoE of 3 with a strong GRADE recommendation (questions 6–8) and the remaining two were assigned an LoE of 2 with a strong GRADE recommendation (questions 9 and 10).Conclusion These consensus-derived recommendations should aid clinical practice and highlight areas of further research for PoCUS in acute settings.
Keywords: clinical practice guidelines; EFSUMB; POCUS; chest ultrasound; point-of-care ultrasound